Evaluation of female factors in infertility by diagnostic laparohysteroscopy in a tertiary health care centre - Garg, Kashish; Paul, Dhruba Prasad; Ray, Jayanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The inability to conceive is one of the most distressing conditions for a couple. It not only makes the female incomplete but also the social taboos attached are phenomenal. The problem of infertility as long as the recorded history of mankind. Fertility in our culture stands for reproductivity, growth and continuity. Reproduction is one of the basic essential for the survival of a species. Diagnostic laparoscopy & hysteroscopy have emerged as an accurate method of assessing, evaluating and treating infertility. Direct visualization of the abdominal and pelvic organs in laparohysteroscopy allows a definitive diagnosis to be made in many conditions where clinical examination and less invasive techniques such as ultrasound and hysterosalpingography fail to identify the problem. Methods: A prospective study was conducted in Department of Obstetrics and Gynaecology, AGMC& GBP Hospital Agartala. 50 infertile women suspected with pelvic (tubal, peritoneal, adnexal) and intrauterine (uterine polyp, septa, submucous fibroid, intrauterine adhesions) pathologies were included in the study for further evaluation and correlation of clinical findings with Laparohysteroscopy observations. Results: Out of 50 cases, 27 (54%) patients had primary infertility. While laparoscopy detected abnormalities in 60% of the cases, significant hysteroscopy findings were noted in 66% of cases. The most common laparoscopic abnormality was tubal (22%) ovarian and peritoneal (16%) in primary and secondary infertile patients respectively. On hysteroscopy, endometrial polyp (30%) was found as the commonest abnormality in both the groups. Conclusions: Laparoscopy and hysteroscopy are both diagnostic and therapeutic procedures. If pathology is discovered, it can often be treated simultaneously. Laparoscopy combined with hysteroscopy is the sole technique to have a direct view of the female reproductive tract and to find out the various causes of infertility.